Mind, brain and narrative - Sanford, A. J. (Anthony J.); Emmott, Catherine (Cambridge : Cambridge University Press, 2012)
'Narratives enable readers to vividly experience fictional and non-fictional contexts. Writers use a variety of language features to control these experiences: they direct readers in how to construct contexts, how to draw inferences and how to identify the key parts of a story. Writers can skilfully convey physical sensations, prompt emotional states, effect moral responses and even alter the readers' attitudes. Mind, Brain and Narrative examines the psychological and neuroscientific evidence for the mechanisms which underlie narrative comprehension. The authors explore the scientific developments which demonstrate the importance of attention, counterfactuals, depth of processing, perspective and embodiment in these processes. In so doing, this timely, interdisciplinary work provides an integrated account of the research which links psychological mechanisms of language comprehension to humanities work on narrative and style'--
Machine generated contents note: List of illustrations; Foreword; Acknowledgements; 1. Narrative and the rhetorical processing framework; 2. Fundamentals of text processing; 3. Multiple levels: counterfactual worlds and figurative language; 4. Attention in text: foregrounding and rhetorical focussing; 5. Rhetorical focussing and depth of processing; 6. The experiential aspect: using embodiment theory; 7. Narrative perspective and the representation of speech and thought; 8. Hot cognition: emotion, empathy and suspense; 9. Narrative's social impact: persuasion and attitude change; 10. Final comments; Appendix 1; Appendix 2; Bibliography; Author index; Subject index.
Includes bibliographical references (pages 274-308) and indexes.
Includes bibliographical references and indexes.
Keywords: Discourse analysis, Narrative -- Psychological aspects; Narration (Rhetoric) -- Psychological aspects; Comprehension; Cognition; Psycholinguistics